Dysphagia in inflammatory myopathies: Self-report, incidence and prevalence - Mulcahy, K.; Langdon, Claire; Mastaglia, F. (Springer New York LLC, 2012)
This study compared self-reported incidence and prevalence of dysphagia in inflammatory myopathy diseases with instrumental data from videofluoroscopy in a cohort of 18 patients with inflammatory myopathies (inclusion body myositis, polymyositis, and dermatomyositis). We found a high self-report of incidence of dysphagia and demonstrated that symptoms described by the patients follow a characteristic pattern. We conclude that there is a high incidence of dysphagia in all three of the inflammatory myopathies. Questions about swallowing should routinely be included in inflammatory myopathy patient examinations in order to appropriately refer patients for further investigation of their swallowing function and avoid the complications associated with dysphagia.